Use of the paired samples (cerebrospinal fluid and serum) in immunodiagnostic of active and inactive human neurocysticercosis - Barcelos, Ivanildes Solange da Costa; Ferreira, Marcelo Simão; Moura, Leandro Pajuaba de; Biondi, Germano Francisco [UNESP]; Costa-Cruz, Julia Maria (FapUNIFESP (SciELO), 2005)
Paired samples of cerebrospinal fluid (CSF) and serum of 30 patients - 10 with active, 10 with inactive neurocysticercosis (NCC), and 10 control subjects - were evaluated by enzyme-linked immunosorbent assay (ELISA) using two Taenia crassiceps metacestode extracts as antigen in order to detect IgG antibodies. In active NCC, high levels of IgG were detected (p < 0.05). The CSF samples showed 80% (CI 72-88) of reactivity in the saline extract (S) and 90% (CI 84-95) in sodium dodecyl sulphate (SDS) and the serum samples were reactive in 90% (CI 84-95) and 100% (CI 98-100) in the S and SDS antigenic extracts, respectively. The use of the paired samples of CSF and serum in active NCC showed equivalent results suggesting that the serum samples could be used as a screening in those patients whose CSF puncture is counter-indicated.
Keywords: Cerebrospinal fluid; Enzyme-linked immunosorbent assay; Neurocysticercosis; Serum; Taenia crassiceps; diagnostic agent; helminth antibody; immunoglobulin G; parasite antigen; animal; blood; case control study; cerebrospinal fluid; comparative study; cross reaction; enzyme linked immunosorbent assay; female; human; immunology; male; neurocysticercosis; Taenia solium; Animals; Antibodies, Helminth; Antigens, Helminth; Case-Control Studies; Cross Reactions; Enzyme-Linked Immunosorbent Assay; Female; Humans; Immunoglobulin G; Male